Voltage-activated adhesion through donor – acceptor dendrimers - Gan, Lu (2020)
Previous investigations on voltage-activated adhesives were restricted to aqueous solvents, where current-directed cross-linking competed with water electrolysis. Replacing aqueous would expand applications of electrocuring technology and avoid excessive foaming, but many organic solvents have high ohmic resistances that prevent electrical conduction. These impediments were overcome through internal grafting of ferrocene (Fc) and diazirine (Dz) donor–acceptor pairs on fifth-generation polyamidoamine (G5-PAMAM) dendrimers, forming G5-Fc-Dz cografted conjugates, where Fc internal additives provided an instantaneous conductive hole (+) network toward the redox conversion of diazirine to carbene insertion adhesion in nontoxic organic solvents of DMSO, DMF, and PEG400. Size exclusion chromatography, 1H NMR, and 19F NMR evaluated the formulations before and after electrocuring to quantitate grafting ratios and cross-linked dendrimers. Cyclic voltammetry confirmed the retained redox behavior of grafted Fc and Dz. Real-time electrorheology established the dependence of cross-linking kinetics and adhesion strength on applied voltage. Liquid G5-Fc15-Dz30 conjugates reached gelation within 2 min and with a storage modulus up to 3.4 ± 0.5 kPa. For the first time, a model system demonstrates the design components necessary toward organic, voltage-activated one-pot adhesives. This has broad implications for adhesives, cosmetics, implantable biomaterials, and flexible biosensors.